Cerclage Plus Adjuvant Vaginal Progesterone for Preterm Birth Prevention in Patients with a Short or Dilated Cervix without Prior Preterm Birth - Hart, Jessica M.; Macharia, Annliz; Modest, Anna M.; Johnson, Katherine M.; Lauring, Julianne; Nicasio, Erica; Hacker, Michele R.; Spiel, Melissa H. (American Journal of Perinatology, 2024)
Objective The primary objective was to determine if vaginal progesterone following cerclage for cervical length <10 mm or cervical dilation in patients without a history of spontaneous preterm birth (sPTB) decreased the risk of preterm birth at <34 weeks' gestation compared with cerclage alone. Secondary objectives were to determine if vaginal progesterone following cerclage (1) decreased the risk of preterm birth at <24, <28, and <37 weeks' gestation and (2) increased the latency period from cerclage placement to delivery compared with treatment with cerclage alone.Study Design Multicenter retrospective cohort study from 2015 to 2020 of singleton pregnancies, without prior sPTB, who had cerclage placement <24 weeks' gestation for cervical length <10 mm or cervical dilation. Exposure defined as cerclage plus vaginal progesterone postoperatively (dual therapy) and unexposed as cerclage alone (monotherapy), based on surgeon preference.Results We included 122 patients, 78 (64%) treated with dual therapy and 44 (36%) treated with monotherapy. In the crude analysis, dual therapy was associated with a lower risk of delivery at <28 weeks' gestation (13%) compared with monotherapy (34%; crude risk ratio: 0.38 [95% confidence interval (CI): 0.19–0.75]). When adjusted for preoperative vaginal progesterone, results were attenuated (adjusted risk ratio: 0.45 [95% CI: 0.20–1.01]). In both the crude and adjusted analyses, the risk of sPTB was not statistically different at <24, <34 or <37 weeks' gestation. Dual therapy was associated with a greater pregnancy latency from cerclage to delivery (16.3 vs. 14.4 weeks; p = 0.04), and greater gestational age at delivery (37.3 vs. 35.8 weeks' gestation; p = 0.02) compared with monotherapy.Conclusion While not statistically significant, the risk of sPTB was lower at all gestational ages studied in patients treated with dual therapy compared with monotherapy. Dual therapy was associated with longer pregnancy latency and greater gestational age at delivery compared with monotherapy.Key Points
Keywords: adjuvant vaginal progesterone; cervical insufficiency; pregnancy latency; short cervical length; cervical cerclage; spontaneous preterm birth; preterm delivery; postoperative vaginal progesterone